MULTIPLE INTELLIGENCES ANAK USIA DINI MENURUT AL-QUR’AN SURAT LUQMAN AYAT 12-19 (Kajian Filsafat Pendidikan) - Nurhadi Nurhadi (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
Multiple Intelligences and spiritual, emotional and intellectual intelligence in the study of Islamic education philosophy are called Imaniyah, Amaliyah and Fikriyah intelligence. This term the author (researcher) concludes from Islamic history about the intelligence of the servants of the Shari'a bearers (the Prophets and the Apostles), the intelligence of the companions of the Prophet and the Messenger of Allah and the intelligence of the ulama (mujtahid fiqh). In Surah Luqman verses 12-19, it contains the subjects of Faith, Aqeedah, Tawheed is Ottoman intelligence. Thanks to Allah Almighty, Prayers, Devotion to Parents is Amaliyah's intelligence. Responsible, Tolerance, Patience, Tawaduk, Amar Ma'ruf, Nahi Mungkar, Ta'at Ibadah are Intellectual intelligence. In accordance with their nature, even though early childhood children are required to receive comprehensive teaching on multiple intelligences because early childhood is naturally fit, therefore parents as teachers must first express that intelligence to their children. In order to wake up and be aware of the potential of our human beings as a servant of Allah SWT. Because early childhood is a golden age for children for the revival of the soul of the afterlife world.